Evaluation of the Usage of SSCS-Based E-Module Among Students - Yuliastrin, Adisti; Vebrianto, Rian; Fiqri, Muhammad; Berlian, Mery (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
Knowledge is an ability that students must possess in solving various problems and applying them in everyday life. This study aimed to determine how far the Effectiveness of knowledge variables for students in the learning process. This study uses the ADDIE development model. with the instrument in the form of a questionnaire consisting of 2 constructs. The survey study was carried out by involving ten teachers from various schools. Data collection techniques were carried out by filling out online questionnaires, which were then analyzed with the help of the SPSS program. The results of the research prove that: 1) the preparation and development of the evaluation of the problem variable instrument in the media for students in this study was carried out by testing two research constructs, namely 1) the accuracy of the variable and 2) the Effectiveness of the variable. As well as the results of testing the validity and reliability indicate that the data validity of the evaluation instrument meets the valid criteria. This research shows that the developed instrument meets the requirements for use in media development in the form of an e-module.